The phenomenological examination of Turkish mothers who have hemophilic sons - Veysel Gök; Sebahat Aydos; Begüm Fatma Kıryar; Alper Özcan; Ebru Yılmaz; Musa Karakükcü; Ekrem Ünal (Trends in Pediatrics, 2025)
Objective: Hemophilia is a coagulation disorder characterized by bleeding episodes that are genetically transmitted from mothers to sons. The disease affects the family psychologically and socially, especially the mothers, who are closely involved in the care of the affected child. We aimed to question the experiences of Turkish mothers with children diagnosed with hemophilia.